Insights into Genetic and Physiological Characteristics of Clover Rhizobia in Afghanistan Soils - Safiullah Habibi; Michiko Yasuda; Shafiqullah Aryan; Tadashi Yokoyama; Kalimullah Saighani; Naoko Ohkama-Ohtsu (Applied Microbiology, 2024)
Livestock production in Afghanistan highly relies on grazing and clover feed, which is a key component of pastures and forage crops. This study elucidated the genetic diversity of clover-nodulating rhizobia in different ecological regions and their effects on clover growth. A total of 57 rhizobia were isolated and their genetic diversities were studied through 16S rRNA and nifD genes. The isolates were inoculated to clover (Afghan local variety), to investigate the potential of nitrogen fixation and influences of clover growth. The 16S rRNA gene analysis showed two distinct groups of Rhizobium (94.7%) and Ensifer (5.3%) species. The nifD phylogenetic relationship revealed a high similarity to Rhizobium and a novel lineage group close to Rhizobium leguminosarum species. In the plant test, different genotypes significantly (p < 0.01) exhibited an increase in plant biomass production, compared to the un-inoculated plants. Among genotypes, the highest plant biomass was recorded in PC8 (1769.0 mg/plant) and PC9 (1409.2 mg/plant) isolates as compared to un-inoculated plants (144.0 mg/plant). Moreover, these isolates showed maximum nitrogen fixation rates of 8.2 and 6.5 µM/plant, respectively. These isolates were identified as the most promising rhizobial strains for developing biofertilizers in the context of Afghanistan.